A contrarreforma no regime de previdência do servidor público civil da União no período de 1998 a 2005 - Pozzi, Maristela Pasolini (2010)
The research concerns itself with the reform of the social security plan for the federal government s civil servants. This reform was pursued as part of the Brazilian State s attempt to adapt to the new reality where financial capital is the centre of economic and social relations within contemporary capitalism. The study analyses the changes implemented in the security system for the federal government s civil servants between 1998 and 2005, reflecting on how the process impacted on security rights and which direction it signals for workers. It presents considerations about the global economic context that motivated the expansion of the financial capital and how that affected Latin American countries. Constrained by the debt crisis of the 1980s, Brazil adhered to the Washington Consensus liberal set of rules, which defined the general direction of the economic policies that would be implemented in the country from the 1990s onwards. According to the tenet of the neoliberal ideology, the interventionist state is deemed inefficient and protectionist, thus it must be reformed and play a smaller role, focused on the market. The social security reform, both for private and public workers, is a particular expression of the State s reform. In the case of civil servants, its outcome was a brutal erosion of rights and brought closer the two security regimes, which were levelled off with weaker rights. Besides, it broadened the space for financial capital, leaving to the market the task to promote complimentary insurance to be financed with pension funds. The shift transferred to workers the risks and costs of their full retirement pensions because a defined contribution scheme was adopted.